TANDUK MAJENG (MADURA’S SONG) AS MEDIA TO IMPROVE ENGLISH SKILL AT PAUD BADRUZ ZAMAN - Farid Abdul Aziz; Taukhid SekhMaulana I (Universitas Madura, 2023)
English learning has been given in formal education, but the methods used are usually less interesting and make some children bored and have difficulty understanding the material presented. Therefore, the implementation of the traditional tanduk majeng song as media in improving English skills at PAUD. Badruz Zaman is expected to make it easy for children to learn English and make learning English fun with interesting method. This activity is carried out for Pre-Primary School so that they have English language skills in vocabulary, language structure, listening and reading. In addition, this activity is also expected to create children who will be ready to compete in the world of education with English language skills.